Antimicrobial activity of endodontic sealers and medications containing chitosan and silver nanoparticles against Enterococcus faecalis - Loyola-Rodriguez, Juan Pablo (2019)
Background: The main microorganism associated with the failure of endodontic treatments is Enterococcus faecalis. Although several endodontic therapeutics have demonstrated antimicrobial activity against E. faecalis, the antimicrobial effectiveness of chitosan (CsNPs) and silver nanoparticles (AgNPs) included into conventional endodontic sealers for endodontic therapies is still unclear. Aim: The objective of this study was to evaluate the antibacterial activity increment (AAI) of endodontic sealers containing CsNPs and AgNPs as well as some chemical components against E. faecalis by direct contact assays. Methods: CsNPs and AgNPs were synthesized by reduction and ionic gelation methods, respectively. Nanoparticles were characterized by dynamic light scattering and energy dispersive X-ray analysis. The bactericidal activity was tested on monolayers on agar plates and collagen membrane surface assays against E. faecalis. Results: The size of CsNPs was 70.6±14.8 nm and zeta potential was 52.0±5.4 mV; the size of AgNPs was 54.2±8.5 nm, and zeta potential was –48.4±6.9 mV. All materials, single or combined, showed an AAI, especially when CsNPs, chlorhexidine (Chx), and the combination of CsNPs-Chx were added. However, the combination of CsNPs-Chx showed the highest (55%) AAI, followed by Chx (35.5%) and CsNPs (11.1%), respectively. There was a significant statistical difference in all comparisons (p < 0.05). Tubliseal (40%) and AH Plus (32%) sealants showed a higher AAI on E. faecalis in the monolayer test and collagen membrane assay analyzed by scanning electron microscopy. Conclusions: Tubliseal and AH plus sealers combined with nanoparticles, especially CsNPs-Chx, could be used for conventional endodontic treatments in the control of E. faecalis bacteria.